2023
DOI: 10.3389/feduc.2022.936724
|View full text |Cite
|
Sign up to set email alerts
|

Learning to innovate: Students and teachers constructing collective innovation practices in a primary school’s makerspace

Abstract: The need to foster citizens’ innovation skills is widely recognized. Although current research acknowledges the potential of makerspaces to promote innovation activities, research still lacks an understanding of underlying mechanisms that can lead the creation of innovations in makerspaces by students. Moreover, research to date has overlooked how innovation practices are formed in K–12 makerspaces. In this sociocultural study, we used ethnographic video data from a Finnish primary school’s makerspace and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…As mentioned above, the targeted junior high school teachers disenthralled themselves from the standardized curriculum and traditional teaching methods with the support of the teacher professional development community and then worked collaboratively to provide their students with an innovative learning style in which they were able to think critically and logically, solve real-life problems interactively and collaboratively, and create freely and reflectively. In addition, this kind of learner-centered and inquirybased movement was authentically valuable in furnishing these adolescents with both scientific inquiry competence and maker competence (i.e., knowledge, attitude, and skills) relevant to technology, aesthetics, and curation with an interdisciplinary STEAM approach, which corresponded with previous perspectives and empirical evidence from different scholars (Halverson and Sheridan, 2014;Chang and Wu, 2018;Oswald and Zhao, 2021;Leskinen et al, 2023;Sun et al, 2023). However, the average mean rating of the maker competence of those 7th-gaders in the control group was only 2.99 (on a 5-point Likert scale), which was not a favorable result.…”
Section: Employing Maker Curriculum Is Successful For Promoting Stude...supporting
confidence: 59%
See 4 more Smart Citations
“…As mentioned above, the targeted junior high school teachers disenthralled themselves from the standardized curriculum and traditional teaching methods with the support of the teacher professional development community and then worked collaboratively to provide their students with an innovative learning style in which they were able to think critically and logically, solve real-life problems interactively and collaboratively, and create freely and reflectively. In addition, this kind of learner-centered and inquirybased movement was authentically valuable in furnishing these adolescents with both scientific inquiry competence and maker competence (i.e., knowledge, attitude, and skills) relevant to technology, aesthetics, and curation with an interdisciplinary STEAM approach, which corresponded with previous perspectives and empirical evidence from different scholars (Halverson and Sheridan, 2014;Chang and Wu, 2018;Oswald and Zhao, 2021;Leskinen et al, 2023;Sun et al, 2023). However, the average mean rating of the maker competence of those 7th-gaders in the control group was only 2.99 (on a 5-point Likert scale), which was not a favorable result.…”
Section: Employing Maker Curriculum Is Successful For Promoting Stude...supporting
confidence: 59%
“…Indeed, the maker movement provides students with new paths for thinking and diverse ways to act, which is beneficial for cultivating their computational thinking (Resnick and Silverman, 2003;Blikstein, 2008). Recent studies indicated that creating a makerspace in which students learn in an enriched environment that emphasizes engagement, communication, practice, and innovation is beneficial for promoting students' maker spirit and competence Oswald and Zhao, 2021;Avendano-Uribe et al, 2022;Hughes et al, 2023;Leskinen et al, 2023). In addition, it is valuable to support and motivate students' learning autonomy (Ryan and Deci, 2000;Barron, 2006;Azevedo, 2011); that is, anyone can learn the skills they require to accomplish what they imagine (Dweck, 2000).…”
Section: Developing Students' Maker Competence For Future Interdiscip...mentioning
confidence: 99%
See 3 more Smart Citations